2023
DOI: 10.17485/ijst/v16i19.2431
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Mechanical and Durability Properties of Concrete Containing Nano Silica, Alccofine and Polypropylene Fibers

MCK Jamenraja,
K Ravichandran

Abstract: Objectives: To evaluate the strength and durability behaviour of concrete specimens that have been reinforced with micro reinforcements made of polypropylene fibers and microfillers and nanofillers such as alccofine and nanosilica, respectively. Methods: The concrete samples were made to achieve a targeted strength of 33 MPa. In this experiment, polypropylene fibers were added to the concrete mix in volume fractions of 0%, 1%, 0.2%, 0.3%, and 0.4%, with the optimum percentages of alccofine (15%) and nanosilica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This may probably be due to the balling of fibres. In Ref (16) , (Jamen Raja MCK et al, 2023), the weight loss in specimens made with fibre was less compared with specimens without fibre. This may be attributed to the inclusion of fibre in concrete.…”
Section: Acid Resistancementioning
confidence: 96%
See 2 more Smart Citations
“…This may probably be due to the balling of fibres. In Ref (16) , (Jamen Raja MCK et al, 2023), the weight loss in specimens made with fibre was less compared with specimens without fibre. This may be attributed to the inclusion of fibre in concrete.…”
Section: Acid Resistancementioning
confidence: 96%
“…et al ( 2022), An increase in porosity was observed with a 0.4% volume fraction of PP fibres owing to the collation of fibres. In Ref (16) , Jamen Raja MCK et al, 2023. The test results showed that as the fibre volume percentage increased, water absorption decreased.…”
Section: Porositymentioning
confidence: 99%
See 1 more Smart Citation